Rapunzel symdrome: gastroduodenal trichobezoar - Loja, David (2003)
Rapunzel syndrome is a rare form of gastric trichobezoar extending to the bowel. It is composed of hair, mucus and decaying food particles. We report the case of an 18 year-old girl who was admitted to our institution with past history of irregular treatment of major depression during the previous year and history of five months of nauseas, vomiting and 15 kg weight loss. On examination findings included abdominal tumor mass, distention and pain. She presented severe anemia and the gastroduodenal x-rays showed gastric filling defects. Diagnosis was confirmed by gastroscopy and gastrotomy revealed a large tricobezoar with duodenal projection, that was removed. She did not present complications on discharge.